LANGUAGE SKILLS, SUB-SKILLS AND VOCABULARIES NEEDED BY AUTOMOTIVE DEPARTMENT STUDENTS OF TECHNICAL HIGH SCHOOL: A NEED ANALYSIS STUDY - Surya Lestari; Syahrial Syahrial; Bambang Suwarno (Universitas Bengkulu, 2017)
This study aimed to analyze specific English language skills and kind of technical vocabulary that are needed by the third year automotive students of SMKN 2 Kota Bengkulu. The sample for interview comprised of 12 alumni, they were teachers and various company officers who have a MOU with SMKN 2 Kota Bengkulu. In the interview was used saturation sample. The results of interview with alumni indicate that the English skill most needed in the workplace is reading, the second was speaking, the third was writing and the last place was listening. The automotive students/ alumni need to comprehend the technical terms associated with technical terms in English. Related to car, are kick lever, oil pump, water cooling system, trail and rolling roof. Related to heavy machine are rear body offset, over hung, road clearance, light van and rear engine. Related to motorcycle are swing arm, bottom link fork, drum brake and kick starter. General automotive vocabulary are disc brake, gasoline, head lamp, piston and tire. Mastery of technical terms greatly affect the practice of industrial work (prakerin) of students in the work place.